Diary of a wimpy kid : Rodrick rules - Kinney, Jeff. (New York : Amulet Books, 2008)
Greg Heffley tells about his summer vacation and his attempts to steer clear of trouble when he returns to middle school and tries to keep his older brother, Rodrick, from telling everyone about Greg's most humiliating experience of the summer.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
Booklist, February 2008.
Bulletin (Center for Children's books), April 2008.
Horn Book, October 2008.
Keywords: Diaries -- Juvenile fiction; Families -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Diaries -- Fiction; Family life -- Fiction; Humorous stories; Middle schools -- Fiction; Schools -- Fiction; Diaries -- Fiction; Family life -- Fiction; Humorous fiction; Middle schools -- Fiction; School stories; Humorous fiction